More than 100 attend the World Sustainable Construction Conference Series 2023 - Nor Azlin, Mohd Azman (UMPSA, 2023)
KUALA LUMPUR, 13 October 2023 - The World Sustainable Construction Conference Series 2023 (WSCC Series 2023), organized by the Faculty of Civil Engineering Technology (FTKA), Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), was held physically from October 13 to 14, 2023 at the Tamu Hotel & Suites, Kuala Lumpur.